Effect of the emission of solid particles from a turbulent slurry film - Lapshin, E. S.; Bulat, A. F.; Blyuss, B.A. (Reports of the National Academy of Sciences of Ukraine, 2014)
The effect of the emission of solid particles from the turbulent flow of a slurry film is experimentally observed. The particle emission begins, when the threshold value of the Reynolds number is attained. The smaller the particle size, the greater the threshold value. The experiments were carried in a vertical cylinder both under laboratory and industrial conditions. The effect can be used in various branches for the purification of liquids from foreign inclusions and was tested in mineral processing technologies.